The Relative Effectiveness of Audio, Video, and Static Visual Computer-Mediated Presentations - LeeSing, A. Curtis; Miles, Carol (Canadian Journal of Education/Revue canadienne de l'éducation, 1999)
Research on non-computerized media such as television, slides, animation, and film has developed an information-processing framework that can be adapted to research on com- puterized media. We examined the relative effectiveness of three different forms of computer presentation: digital video presentations with text, audio-only presentations with text, and static visual presentations with text. ANOVA results showed that although the achievement scores of participants in different treatment groups did not differ signifi- cantly, there was a significant difference in the time participants took to complete the presentations. From an information-processing perspective, these differences may be attributed to bisensory interference or bisensory facilitation. We concluded that when computer-mediated presentations are being designed, the comparative efficiency of the learning medium might often be more pertinent than the effectiveness of media imple- mentation. Les auteurs ont analysé l’efficacité relative de trois formes de présentation informatisée : la présentation vidéo numérique avec texte, la présentation exclusivement audio et la présentation visuelle statique avec texte. Les résultats de l’analyse de la variance révèlent une nette différence dans le temps pris par les participants pour effectuer les présentations. Du point de vue du traitement de l’information, ces différences peuvent s’expliquer par l’interférence bisensorielle ou la facilitation bisensorielle. Les auteurs concluent que, dans les présentations assistées par ordinateur, l’efficience relative du média d’apprentissage peut souvent être considérée plus importante que l’efficacité réelle de l’utilisation du média.